The Influence of Students’ Perceptions of School Counselors’ Personality on Students’ Attitudes Toward Participating in Guidance and Counseling Services at SMP RK Deli Murni Delitua - Grace Melia Sidabukke; Erwita Ika Violina (Era Scientific Publisher, 2025)
This study was motivated by the low level of student participation in guidance and counseling sevices, which is presumed to be related to their perceptions of the counselor’s personality. A positive perception of the counselor’s personality is believed to encourage openness and enthusiasm, while a negative perception may lead to resistance toward counseling services. This study aims to determine the influence of students’ perceptions of the GC teacher’s personality on their attitudes toward participating in GC services at SMP RK Deli Murni Delitua. This research employed a quantitative correlational method with a population of 400 students and a sample of 200 students selected through a simple random sampling technique. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability, and analyzed using simple linear regression assisted by SPSS software. The results showed a positive but weak influence between students’ perceptions of the GC teacher’s personality and their attitudes in participating in GC services, with a correlation coefficient (r) of 0.249 and a determination coefficient of 0.057. This means that students’ perceptions contributed 5.7% to their attitudes, while the remaining 94.3% were influenced by other factors.The study concludes that the more positive students’ perceptions of the GC teacher’s personality, the more positive their attitudes toward counseling services. It is recommended that GC teachers strengthen their interpersonal communication and build warmer relationships with students, and that schools support efforts to improve the image and effectiveness of guidance and counseling services.